Association of body mass index with progression and prediction of multiple sclerosis - Tadić, Daliborka; Đajić, Vlado; Grgić, Sanja; Miljković, Siniša (Scripta Medica, 2020)
Background: Multiple sclerosis is a disease whose etiology involves multifactorial interactions among genetic and environmental factors. Obesity is one of the most important environmental factors conducive to the onset and progression of the disease. The aim of the study was to determine the value of body mass index (BMI) in a population of patients with multiple sclerosis compared to the general population, to assess the relation between the BMI and physical disability in patients with multiple sclerosis and the influence of the BMI on the course and progression of the disease. Material and Methods: A cross-sectional study was done on 100 patients suffering from multiple sclerosis (experimental group) and 50 healthy people (control group). In order to determine the degree of physical disability the Expanded disability status scale (EDSS) was used. Clinical and demographic data and values ​​of the BMI in both studied groups were collected. BMI was defined as the weight in kilograms divided by the surface area measured in square meters. Statistical analysis included the descriptive statistics, t-test, chi- square test, analysis of variance, correlation, and regression analysis. Results: Total body weight and BMI were significantly higher in the control group (p< 0.05). There was no statistically significant correlation between EDSS and BMI (p = 0.574). There was a correlation between the course of MS and whether BMI has an abnormal or normal level (p = 0.031). Normal BMI proved to be a predictive factor (p = 0.086). Conclusion: BMI is an environmental factor that significantly affects the progression and prediction of multiple sclerosis, but not to the degree of physical disability.Keywords: multiple sclerosis, BMI, progression, prediction, physical disability.